2009
DOI: 10.1002/ar.21009
|View full text |Cite
|
Sign up to set email alerts
|

The Normal Genital Tract of the Female California Sea Lion (Zalophus californianus): Cyclic Changes in Histomorphology and Hormone Receptor Distribution

Abstract: Changes in reproductive tract histomorphology, and estrogen (ERa) and progesterone receptor (PR) expression throughout the breeding cycle were evaluated in free-ranging stranded female California sea lions (Zalophus californianus). Hormone receptor expression in the ovaries, uterus, cervix, and vagina was evaluated using an immunohistochemical technique with monoclonal antibodies. During a large portion of the cycle, ovaries contained both a corpora lutea (CL) and follicles in varying stages of development. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Semiquantitative analysis by immunohistological staining suggests that both are substantially lower in the endometrium during diapause, relative to post-implantation gestation. No variation was evident in progesterone receptor abundance in the surface and glandular epithelium between diapause and later gestation in this species (Colegrove et al, 2009). Clearly, further investigation of steroid receptors during gestation and diapause in carnivores is warranted.…”
Section: Mustelid Carnivore Obligate Modelmentioning
confidence: 75%
See 1 more Smart Citation
“…Semiquantitative analysis by immunohistological staining suggests that both are substantially lower in the endometrium during diapause, relative to post-implantation gestation. No variation was evident in progesterone receptor abundance in the surface and glandular epithelium between diapause and later gestation in this species (Colegrove et al, 2009). Clearly, further investigation of steroid receptors during gestation and diapause in carnivores is warranted.…”
Section: Mustelid Carnivore Obligate Modelmentioning
confidence: 75%
“…The same authors demonstrated progesterone receptors to be present in the post-implantation uterus, but no comparisons between diapause and later gestation were made. Progesterone receptors, along with both ESR1 and ESR2 are present in the uterus of the California sea lion (Zalophus calforianus), a pinniped carnivore (Colegrove et al, 2009). Semiquantitative analysis by immunohistological staining suggests that both are substantially lower in the endometrium during diapause, relative to post-implantation gestation.…”
Section: Mustelid Carnivore Obligate Modelmentioning
confidence: 99%
“…The relationship between morphology and seasonal functionality of the reproductive organs in the Otariidea family has been scientifically demonstrated (Colegrove et al 2009a, Colegrove et al 2009b. Based on the possibility that the anatomy of male genital organs relates to the environment and influences reproductive success and conservation status of the species, we hypothesize that special features found in the morphology of A. australis genital organs are related to the unique annual mating season.…”
Section: Introductionmentioning
confidence: 97%
“…The main differential diagnosis for this tumor was California sea lion urogenital carcinoma. However, the pattern of growth and cellular morphology were distinctly different from any of the patterns described for that well-characterized entity (Gulland et al 1996, Colegrove et al 2009a. Additionally, no neoplastic transformation was seen grossly or histologically in the lower urinary or genital tracts, which are the usual primary sites of the urogenital carcinoma.…”
Section: Discussionmentioning
confidence: 57%